Caminhos de uma rede: o percurso do usuário de álcool e outras drogas - Manfrê, Monique Marques [UNESP] (2015)
This study aimed to assess the therapeutic itineraries of users of alcohol and other drugs from a large city in the state of São Paulo and investigate the perception of managers and health workers on the network of health care to the user of alcohol and other drugs and identify which services make this network. A field survey was held from October 2013 to March 2014 in a center of Psychosocial Care alcohol and drugs (CAPSad), Psychiatric Hospital, Primary Care (AB) and Regional Health Directorate (DRS). Survey subjects were four users of alcohol and other drugs, three health workers and three managers. Was used as data collection instrument the interview script opened to the subjects to produce narratives. The results showed that the therapeutic path of participants is plural, contemplating the informal care of family, religious beliefs and professional care, not limited mental health institutions only. The subjects tend to resort simultaneously to several places in search of care. However users circulating in a network of little articulated care, which directly reflects the therapeutic itinerary of these users, fixing them in certain services. We conclude that the network to the user, it is often understood only as specialized services such as CAPSad and places to hospital. Based on the results stands out the need to improve the attention to the user of alcohol and other drugs; through a network of articulated attention to health and that they act in the logic of psychosocial care